Effects of Insulin-Like Growth Factor-1 on Rotenone-InducedApoptosis in Human Lymphocyte Cells (2009)
ABSTRACT: Human peripheral blood lymphocytes have been useful as a putative model of oxidative stress-induced apoptosisfor Parkinson’s disease. The present work shows that rotenone, a mitochondrial complex I inhibitor, induced time- and con-centration-dependent apoptosis in lymphocytes which was mediated by anion superoxide radicals (O2•)) ⁄ hydrogen peroxide,depolarization of mitochondria, caspase-3 activation, concomitantly with the nuclear translocation of transcription factorssuch as NF-jB, p53, c-Jun and nuclei fragmentation. Since insulin-like growth factor-1 (IGF-1) interferes with a cell’s apopto-tic machinery when subjected to several stressful conditions, it is demonstrated here for the first time that IGF-1 effectivelyprotects lymphocytes against rotenone through PI-3K ⁄ Akt activation, down-regulation of p53 and maintenance of mitochon-drial membrane potential independently of ROS generation. These data might contribute to understanding the role played byIGF-1 against oxidative stress stimuli